Association between sleep duration and disability in activities of daily living among Chinese older adults: a nationwide observational study - Cai, Dahuan; Zeng, Yanxin; Chen, Min; Zhong, Yun; Quan, Yilin; Ye, Mengliang; Huang, Xiaoxiao (Frontiers in Public Health, 2025)
BackgroundThis study aims to explore the relationship between sleep duration and Activity of Daily Living (ADL) disability among older adults in China. ADL disability severely impacts the quality of life of older adults and is associated with various physical and mental health issues. With the aging population in China, the burden of ADL disability is increasing.MethodsData were sourced from the 2018 national follow-up of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), including 9,572 participants aged 65 and above. Sleep duration was assessed via self-reported questionnaire and categorized into short (<7 h), medium (7–8 h), and long (≥9 h). ADL disability was evaluated through Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL). Logistic regression models were used to analyze the relationship between sleep duration and ADL disability, with subgroup analyses conducted to explore differences by gender and physical activity.ResultsThe study found a significant non-linear relationship between sleep duration and ADL disability. Compared to older adults with a sleep duration of 7–8 h, those with over 9 h of sleep had a significantly higher risk of BADL and IADL disability (OR = 1.36, OR = 1.35). Subgroup analyses indicated that this relationship existed among older adults of different genders, age, and physical activity levels.ConclusionFor older adults in China, maintaining a sleep duration of 7–8 h may be an effective strategy for preventing ADL disability. Both excessively long and short sleep duration are associated with an increased risk of ADL disability in this population.